Three-dimensional current collector and preparation method thereof and lithium battery
By using three-dimensional current collector in lithium batteries, the problems of dendrites growing and volume expansion of metal lithium anode during circulation are solved, and higher cycle stability and service life are achieved.
Patent Information
- Application Number
- CN202411412699.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-11
AI Technical Summary
The severe dendrites and huge uncontrollable volume expansion of metal lithium anode during the circulation process lead to performance deterioration and safety risks.
Using three-dimensional current collectors, including metal current collector matrix, porous alloy layer and porous carbon layer, a multiple three-dimensional porous structure is formed by annealing treatment, providing lithium deposition space, inhibiting dendrites' growth, and improving conductivity and cyclic stability through the carbon layer. sex.
Effectively inhibit dendrites' growth, alleviate volume expansion, and improve the circulation stability and service life of lithium batteries.
Smart Images

Figure CN118919737B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a three-dimensional current collector and a preparation method thereof, and a lithium battery. Background Art
[0002] Metal lithium anode has a very high theoretical specific capacity. However, the serious dendrite growth problem of metal lithium anode during the cycle not only leads to performance deterioration, but also causes safety risks. Moreover, the huge and uncontrollable volume expansion during the anode deposition process is also an extremely severe challenge for practical applications. In order to solve this problem, a three-dimensional network skeleton is constructed at the anode to provide space for metal lithium deposition, reduce volume expansion, reduce current density, and promote uniform lithium deposition, which is of great significance for the practical application of lithium metal batteries.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] The object of the present invention is to provide a three-dimensional current collector and a preparation method thereof and a lithium battery. The three-dimensional current collector can inhibit dendrite growth and alleviate volume expansion, thereby improving the cycle stability of the battery.
[0005] In order to achieve the above-mentioned object of the present invention, the present invention provides a three-dimensional current collector on the one hand, comprising:
[0006] Metal current collector substrate;
[0007] A porous alloy layer is located on the surface of the metal current collector matrix; the alloy layer includes an MX alloy component, wherein M is a metal element in the metal current collector matrix, and X is selected from an element that can react with lithium to form an alloy;
[0008] A porous carbon layer is located on the surface of the alloy layer; the porous carbon layer is doped with C3N4.
[0009] In some embodiments, the X includes at least one of Zn, Sn, and Bi.
[0010] In some embodiments, the porous alloy layer has an average thickness of 0.2 to 10 μm.
[0011] In some embodiments, the porous carbon layer has an average thickness of 0.4 to 6 μm.
[0012] In some embodiments, the porosity of the three-dimensional current collector is 51% to 87%.
[0013] In some embodiments, the average pore size of the three-dimensional current collector is 0.01-0.3 μm.
[0014] In some embodiments, the metal current collector matrix includes at least one of copper, nickel, aluminum, and stainless steel.
[0015] Another aspect of the present invention provides a method for preparing a three-dimensional current collector, comprising the following steps:
[0016] After coating the slurry on the surface of the metal current collector substrate, annealing is performed;
[0017] The slurry comprises a conductive carbon material, a binder, metal X nanoparticles and a carbon-nitrogen compound; the X is selected from elements that can react with lithium to form an alloy;
[0018] The coating thickness of the slurry is ≤50 μm;
[0019] The annealing treatment includes: annealing at 300-1000° C. for 2-48 hours under a protective atmosphere.
[0020] In some embodiments, in the annealing treatment, the annealing temperature is 500-700° C., and the annealing time is 5-10 hours.
[0021] In some embodiments, based on the total mass of the slurry, the mass content of the conductive carbon material is 0.1% to 70%, the mass content of the binder is 0.5% to 10%, and the mass content of the metal X nanoparticles is 1% to 50%.
[0022] In some embodiments, the content of the carbon-nitrogen-containing compound in the slurry is 10-100 mg / mL. Further, the carbon-nitrogen-containing compound includes dicyandiamide.
[0023] In some embodiments, the conductive carbon material includes at least one of graphite, graphene, carbon nanotubes and conductive carbon black; the binder includes at least one of CMC, SBR, PAA, PAN, PVDF and PTFE; and X includes at least one of Zn, Sn and Bi.
[0024] In some embodiments, the coating thickness of the slurry is 0.5 to 50 μm, preferably 0.5 to 20 μm.
[0025] In some embodiments, the slurry includes a solvent and an additive. Further, the boiling point of the additive is higher than the boiling point of the solvent.
[0026] In some embodiments, the boiling points of the solvent and the additive differ by 50 to 120° C. Further, the solvent includes water, and the additive includes NMP; or, the solvent includes NMP, and the additive includes succinonitrile.
[0027] In some embodiments, the mass of the additive is 1% to 20% relative to the total mass of the slurry.
[0028] Another aspect of the present invention provides a lithium battery, comprising a pole piece, wherein the pole piece comprises any one of the three-dimensional current collectors described above.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The current collector of the present invention has a multiple three-dimensional porous structure, which provides a large amount of space for accommodating lithium deposition, can inhibit dendrite growth and alleviate volume expansion; and has good lithium affinity, can reduce the nucleation barrier and reduce the generation of dendrites; at the same time, the carbon layer on the surface of the current collector, on the one hand, improves the conductivity and reduces polarization, and on the other hand, avoids direct contact between metallic lithium and the electrolyte, thereby improving the cycle stability of the current collector and the battery using the above current collector and extending the service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 A schematic diagram of the structure of a three-dimensional current collector provided by an embodiment of the present invention;
[0033] Figure 2 A schematic diagram of the formation process of a three-dimensional current collector provided by an embodiment of the present invention;
[0034] Figure 3 This is a surface SEM image of the three-dimensional current collector provided in Example 1 of the present invention;
[0035] Figure 4 This is a comparison diagram of deposition overpotentials of batteries corresponding to Example 1 and Comparative Examples 1 to 2 of the present invention;
[0036] Figure 5 It is a comparison chart of the deposition coulomb efficiency of the batteries corresponding to Example 1 of the present invention and Comparative Examples 1-2. DETAILED DESCRIPTION
[0037] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0038] In the description of the present invention, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.
[0039] One embodiment of the present invention provides a three-dimensional current collector. Figure 1 A schematic diagram of the structure of a three-dimensional current collector provided in an embodiment of the present invention, wherein the three-dimensional current collector comprises:
[0040] Metal current collector substrate;
[0041] A porous alloy layer is located on the surface of the metal current collector matrix; the alloy layer includes an MX alloy component, M is a metal element in the metal current collector matrix, and X is selected from an element that can react with lithium to form an alloy;
[0042] The porous carbon layer is located on the surface of the alloy layer; the porous carbon layer is doped with C3N4.
[0043] The three-dimensional current collector of the present invention includes both a three-dimensional porous structure based on an alloy and a three-dimensional structure based on a carbon material, and has multiple three-dimensional structures, which can provide a large amount of space for lithium deposition, inhibit dendrites and alleviate volume expansion. At the same time, the multiple three-dimensional structures have good lithium affinity, which can reduce the nucleation barrier and further reduce the formation of dendrites.
[0044] In addition, the carbon layer on the surface of the current collector, on the one hand, improves conductivity and reduces polarization, and on the other hand, avoids direct contact between metallic lithium and the electrolyte, thereby improving the cycle stability of the current collector and the battery using the above current collector and extending the service life.
[0045] At the same time, C3N4 in the porous carbon layer has excellent lithium affinity, which further reduces the deposition overpotential during lithium deposition and promotes uniform lithium deposition.
[0046] In a specific embodiment of the present invention, X includes at least one of Zn, Sn and Bi.
[0047] When X is any one of Zn, Sn, and Bi, the alloy layer may include M-Zn, M-Sn, or M-Bi, etc., which can induce lithium deposition, reduce deposition overpotential, and promote nucleation of metallic lithium.
[0048] In a specific embodiment of the present invention, the average thickness of the porous alloy layer is 0.2-10 μm, such as 0.5-5 μm.
[0049] For example, in different embodiments, the average thickness of the porous alloy layer may be selected from, but not limited to, 0.2 μm, 0.5 μm, 1 μm, 2 μm, 4 μm, 5 μm, 8 μm, 10 μm, or a range consisting of any two thereof.
[0050] In a specific embodiment of the present invention, the average thickness of the porous carbon layer is 0.4-6 μm.
[0051] For example, in different embodiments, the average thickness of the porous carbon layer may be selected from, but not limited to, 0.4 μm, 0.5 μm, 0.8 μm, 1 μm, 2 μm, 4 μm, 6 μm, or any two thereof.
[0052] In a specific embodiment of the present invention, the porosity of the three-dimensional current collector is 51% to 87%.
[0053] For example, in different embodiments, the porosity of the three-dimensional current collector can be selected from but not limited to 51%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 87% or any two thereof. The porosity of the three-dimensional current collector refers to the porosity of the alloy layer and the carbon layer.
[0054] In a specific embodiment of the present invention, the average pore size of the three-dimensional current collector is 0.01-0.3 μm.
[0055] For example, in different embodiments, the average pore size of the three-dimensional current collector can be selected from, but not limited to, 0.01 μm, 0.05 μm, 0.1 μm, 0.2 μm, 0.3 μm, or any two thereof. Within the above ranges, the porosity and the average pore size can improve the wettability of the electrolyte and reduce the deposition overpotential. The average pore size refers to the average pore size of the porous structure of the alloy layer and the carbon layer.
[0056] In a specific embodiment of the present invention, the metal current collector matrix includes at least one of copper, nickel, aluminum and stainless steel.
[0057] Another aspect of the present invention provides a method for preparing a three-dimensional current collector, comprising the following steps:
[0058] After coating the slurry on the surface of the metal current collector substrate, annealing is performed;
[0059] The slurry includes a conductive carbon material, a binder, metal X nanoparticles and a carbon-nitrogen compound; X is selected from an element that can react with lithium to form an alloy;
[0060] The coating thickness of the slurry is ≤50μm;
[0061] The annealing treatment includes: annealing at 300-1000° C. for 2-48 hours under a protective atmosphere.
[0062] For example, in different embodiments, the temperature of the annealing treatment can be selected from but not limited to 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C or any two thereof; the time of the exit treatment can be selected from but not limited to 2h, 10h, 16h, 24h, 30h, 36h, 40h, 48h or any two thereof. Under the above annealing conditions, the organic components in the slurry are fully carbonized to form a corresponding carbon layer, and the carbon-nitrogen-containing compound is thermally decomposed to form a doped C3N4 compound.
[0063] In actual operation, the metal current collector can adopt a conventional commercial current collector substrate, such as copper foil, nickel foil, aluminum foil, stainless steel foil, etc. Before coating the slurry, it is first cleaned with dilute hydrochloric acid and acetone.
[0064] Figure 2 A schematic diagram of the formation process of a three-dimensional current collector provided in an embodiment of the present invention. It can be seen from the figure that after the corresponding slurry is coated on the surface of the metal current collector substrate, during the annealing process, the organic components in the slurry are carbonized, and the carbon-nitrogen compound is thermally decomposed to form a C3N4-doped carbon coating layer on the surface of the metal current collector substrate. In addition, the metal X nanoparticles in the slurry contact the metal current collector substrate and diffuse with each other based on the Kirkendall effect. Due to different diffusion rates, a large number of holes are formed at the contact interface, thereby forming a porous alloy layer structure on the surface of the metal current collector substrate.
[0065] In a specific embodiment of the present invention, in the annealing treatment, the annealing temperature is 500-700° C., and the annealing time is 5-10 hours.
[0066] In a specific embodiment of the present invention, based on the total mass of the slurry, the mass content of the conductive carbon material is 0.1% to 70%, the mass content of the binder is 0.5% to 10%, and the mass content of the metal X nanoparticles is 1% to 50%.
[0067] For example, in different embodiments, based on the total mass of the slurry, the mass content of the conductive carbon material can be selected from, but not limited to, 0.1%, 0.2%, 0.5%, 1%, 2%, 5%, 10%, 20%, 40%, 50%, 70% or any two of them; the mass content of the binder can be selected from, but not limited to, 0.5%, 1%, 2%, 4%, 5%, 6%, 8%, 10% or any two of them; the mass content of the metal X nanoparticles is 1%, 2%, 5%, 8%, 10%, 15%, 20%, 30%, 40%, 50% or any two of them, such as 5% to 20%. The appropriate amount of conductive carbon material, binder, and metal X nanoparticles helps to form a carbon layer of a certain thickness and alloy appropriately, taking into account the reduction of deposition overpotential and the improvement of average coulomb efficiency.
[0068] In a specific embodiment of the present invention, the content of the carbon-nitrogen compound in the slurry is 10-100 mg / mL. Further, the carbon-nitrogen compound includes at least one of dicyandiamide, melamine and cyanamide.
[0069] For example, in different embodiments, the content of carbon-nitrogen compounds in the slurry can be selected from but not limited to 10 mg / mL, 20 mg / mL, 40 mg / mL, 50 mg / mL, 60 mg / mL, 80 mg / mL, 100 mg / mL or a range consisting of any two of them.
[0070] In a specific embodiment of the present invention, the conductive carbon material includes at least one of graphite, graphene, carbon nanotubes and conductive carbon black; the binder includes at least one of CMC, SBR, PAA, PAN, PVDF and PTFE; and X includes at least one of Zn, Sn and Bi.
[0071] In a specific embodiment of the present invention, the coating thickness of the slurry is 0.5 to 50 μm, preferably 0.5 to 20 μm.
[0072] For example, in different embodiments, the coating thickness of the slurry can be selected from, but not limited to, 0.5 μm, 1 μm, 2 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 20 μm, 30 μm, 40 μm, 50 μm, or any two of them. The appropriate coating thickness can ensure the formation of sufficient alloy layer and carbon layer, and avoid the problem of the surface carbon layer falling off after annealing due to excessive coating.
[0073] In a specific embodiment of the present invention, the slurry includes a solvent and an additive. Further, the boiling point of the additive is higher than the boiling point of the solvent.
[0074] In the slurry of the present invention, a porous structure is formed in the carbon layer by phase separation. The solvent and additive in the slurry play a place-occupying role in the slurry, and form pores after heating and volatilization. Two or more solvents and additives with different boiling points are used. During the annealing process, according to the difference in boiling points, the low-boiling-point solvent evaporates first, and the high-boiling-point additive is still evenly distributed inside, playing a place-occupying role. After the part of the additive volatilizes, pores are formed inside. This method can form a pore structure with uniform pore distribution and moderate pore size. If a single solvent is used, the pore structure depends on the support of the material itself to form, the pore distribution is random and the pore size is uneven, which is not conducive to ion diffusion.
[0075] In a specific embodiment of the present invention, the boiling points of the solvent and the additive differ by 50 to 120° C. Further, the solvent includes water, and the additive includes NMP; or, the solvent includes NMP, and the additive includes succinonitrile.
[0076] In a specific embodiment of the present invention, the mass of the additive is 1% to 20% relative to the total mass of the slurry.
[0077] For example, in different embodiments, the mass of the additive can be selected from, but not limited to, 1%, 2%, 5%, 8%, 10%, 12%, 15%, 18%, 20% or any two thereof, such as 2% to 10%, relative to the total mass of the slurry. The mass of the additive is regulated within the above range, further taking into account the formation of a porous carbon layer with a certain porosity, uniform pore distribution, and moderate pore size, while ensuring the structural stability of the carbon layer.
[0078] In actual operation, after the slurry is coated on the surface of the metal collector substrate, it can be left to stand at room temperature for more than 4 hours, such as 10 to 12 hours, but not limited to this, and then vacuum dried at 80 to 100°C for more than 2 hours, such as 4 to 6 hours, but not limited to this, and then subjected to corresponding annealing treatment.
[0079] Another aspect of the present invention provides a lithium battery, comprising a pole piece, wherein the pole piece comprises any one of the above-mentioned three-dimensional current collectors.
[0080] Among them, the lithium battery can adopt the conventional battery assembly method, and the active material layers of the positive electrode sheet and the negative electrode sheet are conventionally adjusted according to the actual type of lithium battery, which will not be elaborated here.
[0081] Example 1
[0082] This embodiment provides a method for preparing a three-dimensional current collector, comprising the following steps:
[0083] (1) Dispersing carbon nanotubes in deionized water, then adding CMC, dicyandiamide, and then adding metal Sn nanoparticles (average particle size of 50 nm), and ultrasonically dispersing to obtain a uniform and stable substance; then adding NMP, stirring thoroughly, to obtain a slurry;
[0084] Based on the total mass of the slurry, the mass content of carbon nanotubes is 0.4wt%, the mass content of CMC is 2wt%, the mass content of metal Sn nanoparticles is 5wt%, and the mass content of NMP is 2wt%; in the slurry, the content of dicyandiamide is 20mg / mL.
[0085] (2) The slurry obtained in step (1) is coated on the surface of a 10 μm thick copper foil with a coating thickness of 5 μm, left to stand at room temperature for 12 h, then vacuum-baked at 100° C. for 5 h, and then heated at 500° C. for 10 h in an argon environment to obtain a three-dimensional current collector.
[0086] Example 2
[0087] This embodiment provides a method for preparing a three-dimensional current collector, comprising the following steps:
[0088] (1) Graphene is dispersed in deionized water, and then PAA, dicyandiamide, and metal Zn nanoparticles (average particle size of 50 nm) are added, and ultrasonic dispersion is performed to obtain a uniform and stable substance; then NMP is added, and after sufficient stirring, a slurry is obtained;
[0089] Based on the total mass of the slurry, the mass content of graphene is 0.1wt%, the mass content of PAA is 3wt%, the mass content of metal Zn nanoparticles is 10wt%, and the mass content of NMP is 5wt%; in the slurry, the content of dicyandiamide is 40mg / mL.
[0090] (2) The slurry obtained in step (1) is coated on the surface of a 10 μm thick copper foil with a coating thickness of 8 μm, left to stand at room temperature for 12 h, then vacuum-baked at 100°C for 5 h, and then heated at 600°C for 8 h in an argon environment to obtain a three-dimensional current collector.
[0091] Example 3
[0092] This embodiment provides a method for preparing a three-dimensional current collector, comprising the following steps:
[0093] (1) Dispersing conductive carbon black SP into deionized water, then adding PAN, dicyandiamide, and then adding metal Bi nanoparticles (average particle size of 50 nm), and ultrasonically dispersing to obtain a uniform and stable substance; then adding NMP, and stirring thoroughly to obtain a slurry;
[0094] Based on the total mass of the slurry, the mass content of conductive carbon black SP is 1wt%, the mass content of PAN is 1wt%, the mass content of metal Bi nanoparticles is 15wt%, and the mass content of NMP is 3wt%; in the slurry, the content of dicyandiamide is 60mg / mL.
[0095] (2) The slurry obtained in step (1) is coated on the surface of a 10 μm thick copper foil with a coating thickness of 10 μm, left to stand at room temperature for 12 h, then vacuum-baked at 100° C. for 5 h, and then heated at 700° C. for 5 h in an argon environment to obtain a three-dimensional current collector.
[0096] Example 4
[0097] This embodiment provides a method for preparing a three-dimensional current collector, comprising the following steps:
[0098] (1) Ultrafine graphite (D50 < 5 μm) is dispersed in NMP, and then PVDF, dicyandiamide, and then metal Sn nanoparticles (average particle size of 50 nm) are added, and ultrasonic dispersion is performed to obtain a uniform and stable substance; then succinonitrile is added, and after sufficient stirring, a slurry is obtained;
[0099] Based on the total mass of the slurry, the mass content of ultrafine graphite is 40wt%, the mass content of PVDF is 4wt%, the mass content of metal Sn nanoparticles is 20wt%, and the mass content of succinonitrile is 10wt%; in the slurry, the content of dicyandiamide is 40mg / mL.
[0100] (2) The slurry obtained in step (1) is coated on the surface of a 10 μm thick copper foil to a coating thickness of 20 μm, left to stand at room temperature for 12 h, then vacuum-baked at 100° C. for 5 h, and then heated at 550° C. for 8 h in an argon environment to obtain a three-dimensional current collector.
[0101] Example 5
[0102] This embodiment provides a method for preparing a three-dimensional current collector, with reference to Embodiment 1, except that in step (1), the mass content of metal Sn nanoparticles in the slurry is different.
[0103] The mass content of the metal Sn nanoparticles in the slurry of this embodiment is 1 wt %.
[0104] Example 6
[0105] This embodiment provides a method for preparing a three-dimensional current collector, with reference to Embodiment 1, except that in step (1), the mass content of metal Sn nanoparticles in the slurry is different.
[0106] The mass content of the metal Sn nanoparticles in the slurry of this embodiment is 50wt%.
[0107] Example 7
[0108] This embodiment provides a method for preparing a three-dimensional current collector, with reference to Embodiment 1, except that in step (2), the coating thickness of the slurry is different.
[0109] In step (2) of this embodiment, the coating thickness of the slurry is 50 μm.
[0110] Example 8
[0111] This embodiment provides a method for preparing a three-dimensional current collector, which is similar to Embodiment 1, except that in step (2), the temperature of the annealing treatment is different.
[0112] In step (2) of this embodiment, the temperature of the annealing treatment is 300°C.
[0113] Example 9
[0114] This embodiment provides a method for preparing a three-dimensional current collector, with reference to Embodiment 1, except that in step (1), the content of carbon-nitrogen compounds in the slurry is different.
[0115] The content of dicyandiamide containing carbon and nitrogen compounds in the slurry of this embodiment is 10 mg / mL.
[0116] Example 10
[0117] This embodiment provides a method for preparing a three-dimensional current collector, with reference to Embodiment 1, except that in step (1), the content of carbon-nitrogen compounds in the slurry is different.
[0118] The content of the carbon-nitrogen compound dicyandiamide in the slurry of this embodiment is 100 mg / mL.
[0119] Embodiment 11
[0120] This embodiment provides a method for preparing a three-dimensional current collector, with reference to Embodiment 1, except that in step (1), the mass content of NMP in the slurry is different.
[0121] The mass content of NMP in the slurry of this embodiment is 1wt%.
[0122] Example 12
[0123] This embodiment provides a method for preparing a three-dimensional current collector, with reference to Embodiment 1, except that in step (1), the mass content of NMP in the slurry is different.
[0124] The mass content of NMP in the slurry of this embodiment is 20wt%.
[0125] Example 13
[0126] This embodiment provides a method for preparing a three-dimensional current collector, with reference to Example 1, except that in step (1), 2 wt % of NMP is replaced with 2 wt % of anhydrous ethanol.
[0127] Embodiment 14
[0128] This embodiment provides a method for preparing a three-dimensional current collector, with reference to Embodiment 1, except that in step (1), NMP is not added to the slurry.
[0129] Embodiment 15
[0130] This embodiment provides a method for preparing a current collector, referring to Embodiment 1, except that in step (1), the mass content of metal Sn nanoparticles in the slurry is different.
[0131] The mass content of the metal Sn nanoparticles in the slurry of this embodiment is 0.5wt%.
[0132] Example 16
[0133] This embodiment provides a method for preparing a current collector, referring to Embodiment 1, except that in step (1), the mass content of metal Sn nanoparticles in the slurry is different.
[0134] The mass content of the metal Sn nanoparticles in the slurry of this embodiment is 70wt%.
[0135] Embodiment 17
[0136] This embodiment provides a method for preparing a current collector, which is similar to Embodiment 1, except that in step (2), the coating thickness of the slurry is different.
[0137] In step (2) of this embodiment, the coating thickness of the slurry is 80 μm.
[0138] Comparative Example 1
[0139] Comparative Example 1 provides a method for preparing a current collector, referring to Example 1, except that in step (1), dicyandiamide is not added to the slurry.
[0140] Comparative Example 2
[0141] Comparative Example 2 provides a method for preparing a current collector, referring to Example 1, except that in step (1), no metal Sn nanoparticles are added to the slurry.
[0142] Comparative Example 3
[0143] Comparative Example 3 provides a method for preparing a current collector, referring to Example 1, except that in step (2), the temperature of the annealing treatment is different.
[0144] In step (2) of Comparative Example 3, the temperature of the annealing treatment is 200°C.
[0145] Experimental Example 1
[0146] Figure 3 This is a surface SEM image of the three-dimensional current collector prepared in Example 1 of the present invention. In order to compare and illustrate the differences between the current collectors obtained in different embodiments and comparative examples, the thickness, porosity, pore size, etc. of each layer of the current collectors obtained in each embodiment and comparative example are characterized. Among them, the thickness and pore size are determined by SEM microscopic morphology characterization. 30 positions are randomly selected in the SEM image, and the thickness of the alloy layer and the thickness of the carbon layer corresponding to the 30 positions are measured respectively, and the average thickness is calculated respectively; 30 holes are randomly selected in the SEM image, and the sizes of the 30 holes are measured respectively, and the longest diameter of the hole is used as the hole size, and then the average value is calculated as the average pore size; the porosity is determined by the liquid absorption method; wherein, the average pore size and porosity correspond to the overall results of the alloy layer and the carbon layer. The test results are shown in Table 1.
[0147] Table 1 Characterization results of different current collectors
[0148]
[0149] In Table 1, “ / ” indicates that the test results of the corresponding test items are substantially the same as those of Example 1.
[0150] Experimental Example 2
[0151] In order to compare and illustrate the performance differences of the current collectors obtained in different embodiments and comparative examples, the current collectors obtained in each embodiment and comparative example were assembled into Li / Cu half-cells according to the following methods, and then the deposition overpotential and coulombic efficiency of the assembled half-cells were tested. The test results are shown in Figure 4 , Figure 5 And Table 2.
[0152] Li / Cu half-cell assembly: The current collector was punched into a disc with a diameter of 13 mm, a metal lithium sheet with a diameter of 15 mm was used as the counter electrode, and the diaphragm was a 3μm+9μm single-sided ceramic diaphragm. The 2032 model button cell was assembled in an argon-filled glove box. The electrolyte included lithium bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), fluoroethylene carbonate (FEC) and lithium difluorophosphate (LiPO2F2) (the concentration of LiFSI was 1.5 M, the mass fraction of FEC was 5%, and the mass fraction of LiPO2F2 was 0.5%). The assembled half-cell was tested.
[0153] Table 2 Performance test results of half-cells with different current collectors
[0154]
[0155] Figure 4 The first cycle deposition overpotential of the half-cell assembled with the current collectors of Example 1, Comparative Example 1 and Comparative Example 2. As can be seen from the figure, no metal Sn nanoparticles were added in Comparative Example 2, so there was a lack of alloying process during lithium deposition, showing the highest deposition overpotential of 37.8mV; metal Sn nanoparticles were added in Comparative Example 1, and lithium alloying induced lithium deposition, so the deposition overpotential was greatly reduced to 9.0mV, indicating that alloying can promote the nucleation of metal lithium. In Example 1, there was an obvious lithium alloying process, and due to the formation of a lithium-philic C3N4 layer, there was almost no deposition overpotential during the 0V lithium deposition process, which was only 2.8mV. It shows that the three-dimensional current collector constructed by the present invention can significantly reduce the lithium deposition overpotential and promote uniform lithium deposition.
[0156] Figure 5 The deposition coulombic efficiency of the half-cell assembled with the current collectors of Example 1, Comparative Example 1 and Comparative Example 2 is as follows: Example 1 and Comparative Example 1 both show relatively low first efficiency (<85%), while the first efficiency of Comparative Example 2 reaches over 90%. This is due to the irreversible lithium loss caused by the first alloying process, which reduces the first efficiency. However, from the perspective of the average coulombic efficiency, Example 1 reaches 98.54%, while Comparative Example 1 and Comparative Example 2 are only 98.11% and 98.01%, respectively, indicating that the three-dimensional current collector of the present invention can improve the deposition stripping efficiency and reduce the lithium loss during the cycle.
[0157] According to the test results in Table 2, NMP was not added in Example 14, the porosity of the carbon layer was reduced, and the wettability of the electrolyte decreased, resulting in a certain degree of increase in the deposition overpotential. In Example 15, the amount of metal Sn nanoparticles added was relatively small, resulting in a significant increase in the deposition overpotential. In Example 16, an excessive amount of metal Sn nanoparticles was added, which would lead to an excessive alloying reaction and a large number of perforations in the copper foil. Although the deposition overpotential increased slightly, the average coulomb efficiency was greatly reduced. In Example 17, the coating thickness was increased, and the surface protective layer fell off after annealing. In Comparative Example 3, the annealing temperature was lowered, resulting in insufficient decomposition of C3N4 and a low degree of carbonization of the binder. Therefore, the deposition overpotential increased significantly, and the average coulomb efficiency also decreased significantly.
[0158] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A three-dimensional current collector, characterized in that: include: Metal current collector substrate; A porous alloy layer is located on the surface of the metal current collector matrix; the alloy layer includes an MX alloy component, wherein M is a metal element in the metal current collector matrix, and X is selected from an element that can react with lithium to form an alloy; A porous carbon layer is located on the surface of the alloy layer; the porous carbon layer is doped with C3N4; The method for preparing the three-dimensional current collector comprises the following steps: coating the slurry on the surface of the metal current collector substrate, followed by annealing; The slurry comprises a conductive carbon material, a binder, metal X nanoparticles and a carbon-nitrogen compound; the X is selected from elements that can react with lithium to form an alloy; The coating thickness of the slurry is ≤50 μm; The annealing treatment includes: annealing at 300-1000° C. for 2-48 hours under a protective atmosphere.
2. The three-dimensional current collector according to claim 1, characterized in that: The X includes at least one of Zn, Sn and Bi; The metal current collector matrix includes at least one of copper, nickel, aluminum and stainless steel.
3. The three-dimensional current collector according to claim 1, characterized in that: Having at least one of the following characteristics: (1) The average thickness of the porous alloy layer is 0.2 to 10 μm; (2) The average thickness of the porous carbon layer is 0.4 to 6 μm.
4. The three-dimensional current collector according to claim 1, characterized in that: Having at least one of the following characteristics: (1) The porosity of the three-dimensional current collector is 51% to 87%; (2) The average pore size of the three-dimensional current collector is 0.01 to 0.3 μm.
5. The method for preparing a three-dimensional current collector according to any one of claims 1 to 4, characterized in that: The steps include: After coating the slurry on the surface of the metal current collector substrate, annealing is performed; The slurry comprises a conductive carbon material, a binder, metal X nanoparticles and a carbon-nitrogen compound; the X is selected from elements that can react with lithium to form an alloy; The coating thickness of the slurry is ≤50 μm; The annealing treatment includes: annealing at 300-1000° C. for 2-48 hours under a protective atmosphere.
6. The preparation method according to claim 5, characterized in that: In the annealing treatment, the annealing temperature is 500-700° C. and the annealing time is 5-10 hours.
7. The preparation method according to claim 5, characterized in that: The slurry has at least one of the following characteristics: (1) Based on the total mass of the slurry, the mass content of the conductive carbon material is 0.1% to 70%, the mass content of the binder is 0.5% to 10%, and the mass content of the metal X nanoparticles is 1% to 50%; (2) In the slurry, the content of the carbon-nitrogen compound is 10 to 100 mg / mL; (3) the carbon-nitrogen-containing compound comprises at least one of dicyandiamide, melamine and cyanamide; (4) The conductive carbon material includes at least one of graphite, graphene, carbon nanotubes and conductive carbon black; (5) The binder includes at least one of CMC, SBR, PAA, PAN, PVDF and PTFE; (6) The X includes at least one of Zn, Sn and Bi.
8. The preparation method according to claim 5, characterized in that: The slurry includes a solvent and an additive; the boiling point of the additive is higher than that of the solvent.
9. The preparation method according to claim 8, characterized in that: The solvent includes water, and the additive includes NMP; or, the solvent includes NMP, and the additive includes succinonitrile; The mass of the additive is 1% to 20% relative to the total mass of the slurry.
10. A lithium battery, characterized in that: It comprises a pole piece, wherein the pole piece comprises the three-dimensional current collector according to any one of claims 1 to 4 or the three-dimensional current collector prepared by the preparation method according to any one of claims 5 to 9.
Citation Information
Patent Citations
Copper-zinc alloy current collector for inhibiting lithium dendrites
CN108550858A
Carbon-coated porous metal coating current collector, preparation method and lithium battery
CN109509877A
Three-dimensional current collector material for lithium negative electrode as well as preparation method and application of three-dimensional current collector material
CN118335993A